2019
DOI: 10.1124/jpet.118.256222
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Wnt Signal Pathway in the Pathogenesis and Therapeutics of Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic lung disease with progressive airflow limitation and functional decline. The pathogenic mechanisms for this disease include oxidative stress, inflammatory responses, disturbed protease/antiprotease equilibrium, apoptosis/proliferation imbalance, senescence, autophagy, metabolic reprogramming, and mitochondrial dysfunction. The Wnt signaling pathway is an evolutionarily conserved signaling pathway that is abnormal in COPD, including chronic bronchitis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 115 publications
2
20
0
Order By: Relevance
“…However, accumulating evidences have shown that Wnt has been implicated in many types of pulmonary diseases, and a dysregulated Wnt signaling in mature lungs was recognized as a driver that leads to excessive cell proliferation and improper cell differentiation for fibrotic repair [ 36 , 37 ]. Indeed, a reactivated Wnt was identified as a key contributor in the initiation and development of hyperproliferative chronic pulmonary diseases [ 9 , 12 ], such as idiopathic pulmonary fibrosis (IPF) [ 11 , 38 ], asthma [ 39 ], and COPD [ 8 , 11 , 34 , 40 ]. With respect to silicosis, both β -catenin-mediated canonical signaling and β -catenin-independent noncanonical signaling were altered in human airway epithelial cells upon silica stimulation; the Wnt inhibitor SFRP1 and noncanonical ligand Wnt5a were downregulated, while another Wnt inhibitor DKK1 was upregulated [ 13 ], despite the fact that the canonical Wnt/ β -catenin signaling was reactivated in silicosis lungs [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, accumulating evidences have shown that Wnt has been implicated in many types of pulmonary diseases, and a dysregulated Wnt signaling in mature lungs was recognized as a driver that leads to excessive cell proliferation and improper cell differentiation for fibrotic repair [ 36 , 37 ]. Indeed, a reactivated Wnt was identified as a key contributor in the initiation and development of hyperproliferative chronic pulmonary diseases [ 9 , 12 ], such as idiopathic pulmonary fibrosis (IPF) [ 11 , 38 ], asthma [ 39 ], and COPD [ 8 , 11 , 34 , 40 ]. With respect to silicosis, both β -catenin-mediated canonical signaling and β -catenin-independent noncanonical signaling were altered in human airway epithelial cells upon silica stimulation; the Wnt inhibitor SFRP1 and noncanonical ligand Wnt5a were downregulated, while another Wnt inhibitor DKK1 was upregulated [ 13 ], despite the fact that the canonical Wnt/ β -catenin signaling was reactivated in silicosis lungs [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to that demonstrated in other chronic lung diseases, the pathogenesis of silicosis is controlled by interactions between various cellular signaling pathways [ 7 10 ]. Among them, the wingless-type MMTV-integration site (Wnt)/ β -catenin signaling, a well-known critical cellular signaling pathway in embryonic development and tissue homeostasis, is reactivated in many chronic pulmonary diseases, including silicosis [ 8 , 9 , 11 13 ]. A blocking of Wnt/ β -catenin signaling alleviated the lung inflammation and fibrosis in silica-induced mouse and rat silicosis models [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Age associated epigenetic variation may additionally reveal genes further disrupted in age associated lung diseases such as COPD. In our fetal lung aDMPs, we found previously discussed differentially methylated age-associations identified in fetal brain tissue [ 13 ] including the Wnt antagonist SFRP1 known to be differentially methylated in adults with asthma [ 41 ] and previously associated with emphysema [ 42 ], nuclear receptor gene NR4A2 crucial for neurogenesis and SHANK2 implicated in neurodevelopmental disorders such as autism and severe asthma [ 13 , 43 ]. ELOVL2 is a consistently identified biomarker for aging [ 12 ] further supported by our finding of association of the age-related ELOVL2 gene and the rapid hypermethylation of its promoter cg16867657 [ 25 , 44 ].…”
Section: Discussionmentioning
confidence: 97%
“…The typical phenotype is the increase of monocytes, lymphocytes, and neutrophils, leading to changes in lung airways and alveoli (3,4). The pathogenesis of COPD includes oxidative stress, inflammation, protease/ antiprotease disorders, apoptosis/proliferation imbalance, aging, autophagy, metabolic disorders, and mitochondrial dysfunction (5,6). Timely treatment can improve the deterioration of the condition, but there is no cure to date.…”
Section: Introductionmentioning
confidence: 99%